Transparência na gestão pública municipal: uma avaliação dos municípios do estado do Rio Grande do Sul - Müller, Andressa Petry (2020)
Transparency is a fundamental aspect for public administration, because it is from it that government information is disclosed and exposed to society as a whole, it also aims to contribute to the control and improvement of the management of public resources, assisting with political issues, providing a greater reach of democracy. Similarly, in order for transparency to act in the right way, it is necessary that there is governance, which guarantees the correspondence of collective expectations, in order to promote the participation of citizens and the appropriate dissemination of information, aiming at monitoring the government's performance. Such action of individuals is ensured by the Law on Access to Information, which legally determines the right to access public data, which must be disclosed on transparency portals, having as an ally the technologies of access to information, which facilitate the access of information by all interested parties. Therefore, through access to information, the population can monitor whether a government is experiencing difficulties, which is noted with Rio Grande do Sul, a state that faces financial problems, going through a fiscal crisis. In view of this, the present study aims to determine the level of transparency that the municipalities of the state of Rio Grande do Sul have, identifying the variables that explain it. For this, a documentary research and analysis is carried out, observing the most recent information published in the gaucho transparency portals, identifying whether there is the correct disclosure of data, and the necessary aspects, based on the Municipal Public Management Transparency Index, as well as by regression analysis and descriptive statistics, using tools such as Excel, SPSS and GRETL. Thus, it is possible to observe that most municipalities in the state have an average level of transparency, with few municipalities having a very high level of transparency, in addition to nineteen municipalities showing a very low level of transparency, which demonstrates that much still needs to be done. be done on the issue of transparency. In addition, it was observed that of the eleven socioeconomic variables analyzed, only five are able to influence the transparency index observed in the cities of Rio Grande do Sul, the Municipal Human Development Index (MHDI) and the size of the municipality, which have a positive impact on the ITGP-M, in addition to the schooling rate, the municipality's expenses and the age proportion of the elderly population, which have a negative impact compared to the ITGP-M. Therefore, it is clear that many measures still need to be adopted by the municipal administrations of Rio Grande do Sul, in order to comply with the Access to Information Law and to attend to all aspects arising from transparency.